Sirenomelia or â€œmermaid syndromeâ€: an extremely rare case in Indonesiasia - Qodri Santosa; Setya Dian Kartika; Irwan Nuryadin; Alfi Muntafiah (Paediatrica Indonesiana, 2023)
Sirenomelia, also known as mermaid syndrome, is a very rare lethal congenital disorder with multisystem malformations, characterized by fusion of the lower limbs. Here we report a preterm neonate with fusion of the lower limbs. The baby was born by cesarean section to a 27-year-old primigravida mother at 35 weeks and 3 daysâ€™ gestation. There was no maternal history of hypertension, heart disease, asthma, or diabetes mellitus. At birth, the infant did not cry, had weak tone, a heart rate (HR) of <60 beats per minute (BPM), an Apgar score of 1/2, and a birth weight of 2,300 grams. The infant had an imperforate anus and no urogenital openings or external genitalia. There was a small penis-like protrusion without an aperture, such as in cases of ambiguous genitalia. The two lower limbs were fused, with five toes on each foot. Despite neonatal resuscitation, the infant died within 75 minutes of birth. The child was diagnosed with sirenomelia. This case report aims to emphasize the importance of early prenatal diagnosis and education of the patientâ€™s family.